A Healthcare Wearable Device for Elderly People - Nguyen, Minh Duc; Tran, Hai Nam; Do, Hanh (Old Journal, 2018)
The aging index of Viet Nam population has increased as well as the number of increasing of single elderly people in the past years pose challenges for medical services of healthcare for them. In this paper, we propose a wearable device which has the capability of measuring some basic bio-signals of the elderly such as temperature, heart rate and monitoring their daily activities in order to detect the falls and accident location in both of indoor and outdoor environment. Moreover, this device is able to remind the elderly about their daily tasks as doing exercises or taking medications which they may easily forget by their senile dementia. If the abnormalities such as temperature, heart rate suddenly changing or the occurrence of falls are detected, the emergency request is sent immediately from the wearable device to hotline of nearby hospital, with the purpose to reduce the meantime between the incidents and help arrival. Reducing the response time to initiate the appropriate patient care may imply simultaneously in reductions of morbidity or mortality rates.